2014
DOI: 10.1038/cddis.2014.110
|View full text |Cite
|
Sign up to set email alerts
|

MiR-19a/b modulate the metastasis of gastric cancer cells by targeting the tumour suppressor MXD1

Abstract: The microRNAs 19a and 19b, hereafter collectively referred to as miR-19a/b, were recognised to be the most important miRNAs in the oncomiRs—miR-17-92 cluster. However, the exact roles of miR-19a/b in cancers have not been elucidated. In the present study, miR-19a/b was found to be over-expressed in gastric cancer tissues and significantly associated with the patients' metastasis of gastric cancer. Using gain or loss-of-function in in vitro and in vivo experiments, a pro-metastatic function of miR-19a/b was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
97
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 30 publications
2
97
1
Order By: Relevance
“…It has been reported that miR-19 was dysregulated in various cancers, and miR-19 upregulation strongly correlated with gain of invasive and metastatic properties and poor prognosis of patients with NSCLC, [11][12][13] gastric cancer, 14 and esophageal squamous cell carcinoma. 15 Moreover, the expression of miR-19 was significantly higher in the lessinvasive breast cancer MCF7 cells than the more-invasive MDAMB-231 cells, and the expression of a positive regulator of tumor angiogenesis and metastasis was negatively regulated by miR-19 in breast cancer cells, 35 suggesting that miR-19 inhibited the metastasis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that miR-19 was dysregulated in various cancers, and miR-19 upregulation strongly correlated with gain of invasive and metastatic properties and poor prognosis of patients with NSCLC, [11][12][13] gastric cancer, 14 and esophageal squamous cell carcinoma. 15 Moreover, the expression of miR-19 was significantly higher in the lessinvasive breast cancer MCF7 cells than the more-invasive MDAMB-231 cells, and the expression of a positive regulator of tumor angiogenesis and metastasis was negatively regulated by miR-19 in breast cancer cells, 35 suggesting that miR-19 inhibited the metastasis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported that upregulation of miR-19a and miR-19b-1 was associated with cancer invasion and metastasis, and poor prognosis of patients with early non-small-cell lung carcinoma (NSCLC), [11][12][13] gastric cancer, 14 and esophageal squamous cell carcinoma. 15 In addition, high levels of serum miR-19a and miR-19b-1 were considered as independent prognostic factors for poor survival of NSCLC patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…MiR‐17‐92 cluster is regarded as the first miRNA cluster with oncogenic potential,15 the cluster includes 6 single mature miRNAs, miR‐19 has been supposed to be the key oncogenic miRNA among the six members of miR‐17‐92 cluster. MiR‐19 is located on chromosome 13 in c13orf25 16 and its expression is up‐regulated in bladder cancer, breast cancer, pancreatic cancer, gastric cancer and laryngeal squamous cell carcinoma 17, 18, 19, 20, 21. MiR‐19 promotes tumourigenesis by regulating target genes and related signalling pathways.…”
Section: Introductionmentioning
confidence: 99%